Aortopulmonary collaterals: An etiology for pediatric tracheostomy hemorrhage. (July 2022) - Stramiello, Joshua A.; Friesen, Tzyynong L.; Rao, Aparna; Ratnayaka, Kanishka; Moore, John; El-Said, Howaida; Brigger, Matthew T.
Abstract: Objective: To report a single-institution's experience of symptomatic aortopulmonary collaterals presenting as tracheostomy tube hemorrhage. Study design: Retrospective case series and Contemporary Review. Setting: Tertiary care children's hospital. Methods: Retrospective review, from 2015 to 2020, of patients <18 years old who were treated for tracheostomy hemorrhage with endovascular embolization of aortopulmonary collateral (APC) vessels. Results: 4 patients were identified, 2 males and 2 females, ages 15 months-to 14 years-old, with a range of cyanotic congenital heart diseases. Direct laryngoscopy and bronchoscopy were necessary for excluding proximal airway sources. Chest computed tomography angiography did not localize pulmonary hemorrhage, but helped identify aortopulmonary collaterals. Cardiac catheterization was both diagnostic and therapeutic with use of endovascular embolization techniques by pediatric interventional cardiology and interventional radiology. Previously reported APC-related pulmonary hemorrhages occurred in significantly different settings compared to our patients, and evaluation by an otolaryngologist was key to rule out upper airway etiologies. Conclusion: Symptomatic aortopulmonary collaterals is an important etiology in pediatric tracheostomy tube hemorrhage in patients with cyanotic congenital heart disease. Highlights: Aorotopulmonary collateral-related tracheostomy hemorrhage in pediatric patients can occur months to years after major cardiac surgery. Otolaryngology evaluation is essential to rule out other causes of pediatric tracheostomy hemorrhage in the setting of aortopulomonary collaterals. Arterial chest computed tomography is helpful in identifying aortopulmonary collaterals and ruling out tracheoinnominate fistula. Cardiac catheterization with fluoroscopy is both diagnostic and therapeutic for aorotopulmonary collateral-related tracheostomy hemorrhage.